Analysis of Handling Pornography Addicts in Rehabilitasi Kunci Yogyakarta - Rini Syamsul; Nurjannah (IRDH International Journal of Social Sciences & Humanities, 2025)
The handling of residents is handled through a religious approach, namely with a divine approach adopted by the resident. Therefore, it is important to examine how the religious approach is in handling pornography addicts in Rehabilitasi Kunci Yogyakarta. The purpose of this study focuses on analyzing how the religious approach is in handling pornography addicts in Rehabilitasi Kunci Yogyakarta. This study is qualitative with a descriptive approach conducting in depth interviews with non-Muslim residents who have undergone rehabilitation at Rehabilitasi Kunci Yogyakarta. Data were collected through interviews, observations and documentation. The results of this study are that the analysis of cases of students undergoing rehabilitation at Rehabilitasi Kunci Yogyakarta highlights the complex journey in handling addiction and behavioral recovery. Initially, the tragic case of sexual harassment in Kalimantan led to legal action and a peace agreement with the victim's family. However, challenges reappeared in Yogyakarta with uncontrolled behavior, triggering the placement of students at Rehabilitasi Kunci Yogyakarta. This program not only focuses on stopping addictive behavior, but also develops social skills and emotional management through group counseling and spiritual guidance. Although its spiritual approach builds a moral foundation and social support, the risk of relapse remains. Overall, this rehabilitation aims to build a solid foundation for a balanced and meaningful life in the future, despite challenges such as the availability of adequate specialists.